2022
DOI: 10.1371/journal.pone.0271358
|View full text |Cite
|
Sign up to set email alerts
|

ICU strain and outcome in COVID-19 patients—A multicenter retrospective observational study

Abstract: Purpose To compare the characteristics, management, and prognosis of patients admitted to intensive care units (ICU) for coronavirus disease (COVID)-19 during the first two waves of the outbreak and to evaluate the relationship between ICU strain (ICU demand due to COVID-19 admissions) and mortality. Methods In a multicentre retrospective study, 1166 COVID-19 patients admitted to five ICUs in France between 20 February and 31 December 2020 were included. Data were collected at each ICU from medical records. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Although the Korean government mobilized infectious wards and intensive care beds to prepare for further epidemics, an unprecedented increase of COVID-19 patients since June 2021 (Figure S 1 ) may induce a shortage in the capability for critical care management, which may eventually increase the mortality of emergent COVID-19 and non-COVID-19 disease patients [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the Korean government mobilized infectious wards and intensive care beds to prepare for further epidemics, an unprecedented increase of COVID-19 patients since June 2021 (Figure S 1 ) may induce a shortage in the capability for critical care management, which may eventually increase the mortality of emergent COVID-19 and non-COVID-19 disease patients [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recent COVID-19 pandemic strained ICU resources throughout the world with adverse effects to patient outcomes (35, 36). At the hospital examined in this study, two findings associated with the higher intensity model were particularly helpful during local surges.…”
Section: Discussionmentioning
confidence: 99%
“…Across the included 39 studies, there were 37 unique measures as shown in Tables 1 and 2. Of these, eleven (three from LMIC) tracked total hospital or ICU caseload unadjusted for baseline bed capacity (14,16,20,22,(25)(26)(27)(28)(29)(30)(31). Caseload was counted as either total census of all patients, total COVID-19-only patients, total positive or person under investigation, or only new admissions on the day of admission (30), daily (20,26,28), weekly (14,25), monthly (29), or quarterly (22).…”
Section: Measures Of Hospital Surge Strainmentioning
confidence: 99%